Optical Properties of Nanostructured Silver Embedded by Electro-Thermo-Diffusion in Opal Photonic Crystal (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Novel nanocomposite materials Ag / opal have been prepared by electro-thermo-diffusion of silver in opal template. Optical properties of these photonic crystals have been studied by angle-resolved reflectance spectroscopy. Interpretation of the observed optical spectra has been made on the basis of the Bragg diffraction and the Fano resonancebetween diffracted in Ag / opal composite photonic crystal electromagnetic waves and those resonantly scattered by silver dendrites.